2010
DOI: 10.1186/1477-7827-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum protein 29 (ERp29), a protein related to sperm maturation is involved in sperm-oocyte fusion in mouse

Abstract: BackgroundSperm-oocyte fusion is a critical step in fertilization, which requires a series of proteins from both spermatozoa and oocyte to mediate membrane adhesion and subsequent fusion. A rat spermatozoa membrane protein is endoplasmic reticulum protein 29 (ERp29), which significantly increases on the sperm surface as well as in the cytoplasm of epididymal epithelia from caput to cauda as the sperm undergo epididymal maturation. Moreover, ERp29 facilitates viral infection via mediating membrane penetration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Sperm surface proteins (O'Rand et al 1984;Burks et al 1995;Cohen et al 1996;Lea et al 1996;Hamatani et al 2000;Yang et al 2010;Ying et al 2010) and seminal plasma proteins (Killian et al 1993;Capkova and Peknicova 1997) have been associated with fertility (O'Rand et al 1984), but in most cases, these proteins were related to fertility based on the demonstration of sperm-egg binding in vitro. In contrast, the expression of a membrane-bound sperm protein at 22 kDa (SP22) has been shown to be associated with fertility in the rat using both in vivo and in vitro models (Klinefelter et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm surface proteins (O'Rand et al 1984;Burks et al 1995;Cohen et al 1996;Lea et al 1996;Hamatani et al 2000;Yang et al 2010;Ying et al 2010) and seminal plasma proteins (Killian et al 1993;Capkova and Peknicova 1997) have been associated with fertility (O'Rand et al 1984), but in most cases, these proteins were related to fertility based on the demonstration of sperm-egg binding in vitro. In contrast, the expression of a membrane-bound sperm protein at 22 kDa (SP22) has been shown to be associated with fertility in the rat using both in vivo and in vitro models (Klinefelter et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies on gene expression have shown genetic responses to pollutants in eel [31-36]. However, large-scale transcriptomic approaches in the European eel have been limited to the study of osmoregulation [37] and comparative gene expression analysis between sympatric European and American eel larvae in the Sargasso Sea [38].…”
Section: Introductionmentioning
confidence: 99%
“…[ 25,26 ] In addition, ERp29 is a crucial factor involved in sperm fertilization via facilitating sperm‐oocyte membrane fusion. [ 27 ] The main findings of our study are as follows: the upregulation of ERp29 was identified in the severe pre‐eclamptic placentas, and the upregulation of ERp29 could block HTR‐8/SVneo cell metastasis, while downregulation of ERp29 had the opposite effect.…”
Section: Discussionmentioning
confidence: 78%